2013
DOI: 10.18537/mskn.04.01.01
|View full text |Cite
|
Sign up to set email alerts
|

Student reading behaviors and preferences at public and private universities in Ecuador: A comparative study

Abstract: Reading compliance is reading assigned course materials in preparation for class. Previous research in university settings in the US suggests that compliance with a professor's request to prepare for class among undergraduate students is low. This paper reports on a study conducted among undergraduate students at the Universities of Cuenca and Azuay in Cuenca, Ecuador to assess their reading behaviors and preferences as well as the factors that influence their decisions to comply or not comply with their profe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Student reading behavior and reading comprehension are global higher education issues (Arrieta and Meza, 2005; Calderon and Quijano, 2010; Moreyra, 1998; Van Hoof et al, 2013) that have educators concerned and scrambling for answers. It is our collective responsibility as researchers and educators to continue our quest to find answers, whether it is in our classrooms, in our students, in our cultures and societies, or in the issues surrounding them.…”
Section: Discussionmentioning
confidence: 99%
“…Student reading behavior and reading comprehension are global higher education issues (Arrieta and Meza, 2005; Calderon and Quijano, 2010; Moreyra, 1998; Van Hoof et al, 2013) that have educators concerned and scrambling for answers. It is our collective responsibility as researchers and educators to continue our quest to find answers, whether it is in our classrooms, in our students, in our cultures and societies, or in the issues surrounding them.…”
Section: Discussionmentioning
confidence: 99%
“…Given the scarcity of English literature on the topic related to the South American setting, the nature of the study reported here was primarily exploratory. The survey was designed to determine professors' reading and research behaviors, and was partially inspired by an analogue study on the assessment of the reading behaviors of students in both universities (Van Hoof et al, 2013b). In comparing professors' behaviors at a public and a private university in Cuenca, the study hoped to find out 1) how much professors read in preparation for their classes and in connection with their research interests; 2) what factors might influence their research behaviors; 3) if any of the observed differences of behavior between professors at the two universities were significantly different; and 4) what universities might do to stimulate the research and reading activities of their professors.…”
Section: The Instrumentmentioning
confidence: 99%